(untitled) (Journal of Global Arts Studies, 2024)
Background: Only Tibetan gold and bronze founding master statues that have endured for centuries without losing their "authentic essence" can elucidate the social and cultural values of their era. Objective: This study explores the origin of statues of Tsongkhapa (also known as the supreme master) from the Gelug sect, showcasing the beauty of their "authentic essence," their artistic allure, and their supreme Buddha nature, which stands out among many. It delves into the profound impact and exemplary role of the craftsmanship and artistry of statues of eminent monks and scholars. Methods: The approach involves using the "true" image of the founding masters as models, crafting with precision, accurate proportions, and masterful techniques. It integrates and blends the imaginative "visions" of deities from Indian Vajrayana and Kalachakra tantric practices, along with local primal deities, Chinese deities, and Mongolian deities. Results: Whether the statues of founding masters are luxurious or simple, crafted for the court or in Tibetan and Han regions, they prioritize humanity and authenticity, adhering to an unwavering standard. Conclusion: The statues of eminent monks and scholars radiate a friendly demeanor and an aura of dignity. In their graceful and confident style, the brilliance of Buddha nature shines through. The exquisite artistic charm and profound religious cultural traits of the gold and bronze founding master statues highlight the unique tension and flair of the people of the Tibetan Plateau.